Gluten and its relationship with inflammation and Parkinson's Disease: A literature review - Zohaer Muttalib; Dana Aboukhalil; Chisom Nwosu; Dave D. Manguerra; Jimmy Wen; Ubaid Ansari; Meraj Alam; Ihab Abed; Ethan Tabaie; Ahmed Salem; Forshing Lui (AIMS Neuroscience)
Parkinson's Disease is a neurodegenerative central nervous system (CNS) disease that primarily affects the dopaminergic cells of the Substantia Nigra in the midbrain and causes a diverse array of symptoms, including dystonia, a loss of balance, difficulty initiating movements, akinesia, muscle spasms, and tremors. It has long been known that environmental and commercial compounds are linked to an increased risk of Parkinson's Disease. Of importance, gluten, a complex polysaccharide, has been hypothesized to cause some of the symptoms related to Parkinson's Disease. It is hypothesized that gluten causes a chronic inflammatory state which may lead to plaque formation and neuronal cell death in the substantia nigra, alongside the symptoms of Parkinson's Disease. This literature review hopes to explore the relationship gluten has as an inflammatory molecule and its role in the production and prolongation of the disease processes in Parkinson's Disease.